Participation and other ethical considerations in participatory action research in post-earthquake rural Haiti. (September 2015) - Pyles, Loretta
This article offers reflections on work with rural peasant organizations in Haiti to build capacities to engage in participatory action research (PAR) and sustainable community recovery and development after the 12 January 2010 earthquake. Specifically, it is based on the perspectives of an engaged scholar who has conducted ongoing research and transnational recovery and development projects in collaboration with rural disaster survivors. Drawing from Pretty's framework for participation, the researcher engages in a retrospective analysis using critical ethnographic methods to problematize the processes seeking to make transparent the ethical tensions around participation, power, language, gender/race/class, outcomes, and institutions.